Standard preoperative use of nonopioid multi‐modal medications for patients undergoing mastectomy with immediate reconstruction and the effect on postoperative opioid needs. Issue 5 (3rd March 2020) - Serpico, Victoria; Mone, Mary; Zhang, Chong; Presson, Angela; Matsen, Cindy; Junkins, Scott; Killian, Heather; Porretta, Jane; Agarwal, Jayant; Nelson, Edward
Abstract: Standardized nonopioid preoperative protocol effects perioperative opioids. Combined use of a cetaminophen, p regabalin, c elecoxib, and transdermal s copolamine (APCS), in mastectomy with immediate subpectoral reconstruction procedures. Retrospective (2014‐2017) cohort study (n = 305) examined treatment groups; APCS, no treatment (NONE), and partial combination APCS (OTHER), employing multivariable gamma regression models controlling preoperative and perioperative variables, examining postoperative opioid use (oral morphine equivalents, OME) and hospital stay (hours, LOS). APCS group had a 25% statistical reduction in OME total vs OTHER, a 12% statistical reduction in LOS vs OTHER, and 11% statistical reduction in LOS vs NONE. Standardized nonopioid preoperative protocol provides insight into perioperative opioid use.